Analisis Keselamatan Lalu Lintas Jalan Tol Ngawi-Kertosono, Studi Kasus Ruas Madiun-Caruban dan Ruas Caruban-Wilangan - Beti Irma Sari (Rekayasa Sipil, 2020)
Toll roads can reduce travel time to be shorter, easier, more convenient, and smooth. However, many road users neglact safety because it’s too comfortable with road conditions that are straight, smooth, and without obstacles. Many road users who drive vehicles exceed the required traffic signs, causing traffic accident. Within 10 months of the operation of the Ngawi-Kertosono toll road on April 1, 2018, until February 24, 2019, traffic accidents reached 59 accidents on the Madiun-Wilangan toll road. From these data, it’s necessary to study the causes of toll road traffic accidents in accident-prone areas. As a first step, it’s necessary to determine the black site and black spots and the relationship between the geometric factors of the road to reduce the number of traffic accidents on the Madiun-Wilangan toll road. This calculation analysis uses the Z-Score and Cusum method by finding the black spot and black site areas. Based on the results of the analysis there are accident-prone areas on the toll road that is from KM 602 to 622 where the Z-Score is 1.733> 0 and Cusum 7.64> 0 so that the accident-prone area can be found on the Black Site and Black Spot results on the road location Madiun, Caruban and Caruban-Wilangan toll road. Suggestions from research need to be conducted outreach or outreach related to traffic and road safety regulations that often have accidents.